Reactivation of hepatitis B in patients of chronic hepatitis C with hepatitis B virus infection treated with direct acting antivirals. Issue 10 (26th September 2017) - Yeh, Ming‐Lun; Huang, Chung‐Feng; Hsieh, Meng‐Hsuan; Ko, Yu‐Min; Chen, Kuan‐Yu; Liu, Ta‐Wei; Lin, Yi‐Hung; Liang, Po‐Cheng; Hsieh, Ming‐Yen; Lin, Zu‐Yau; Chen, Shinn‐Cherng; Huang, Ching‐I; et al.
Abstract: Background and Aim: Hepatitis B virus (HBV) may reactivate when treating chronic hepatitis C (CHC) with direct acting antivirals (DAA). We aim to investigate the risk of HBV reactivation during DAA therapy. Methods: Chronic hepatitis C patients receiving pan‐oral DAA therapy from December 2013 to August 2016 were evaluated. Fifty‐seven patients that had a past HBV infection (negative hepatitis B surface antigen [HBsAg] and positive hepatitis B core antibody) and seven patients that had a current HBV infection (positive HBsAg) were enrolled. Serum HBV and hepatitis C virus (HCV) markers were regularly measured. The endpoints were the HCV sustained virological response (SVR) and the HBV virological/clinical reactivation. Results: The overall SVR12 rate was 96.9%, and two patients, one with positive HBsAg, had a relapse of HCV. No episodes of HBV virological reactivation were observed among the patients with a past HBV infection. For the seven patients with a current HBV infection, HBV virological reactivation was found in four (57.1%) of the seven patients. Clinical reactivation of HBV was observed in one patient with pretreatment detectable HBV DNA and recovered after entecavir administration. For the other three patients with HBV virological reactivation, the reappearance of low level HBV DNA without clinical reactivation was observed. HBsAg levels demonstrated only small fluctuations in all the patients. Conclusions: There was a minimal impact of hepatitis B core antibody seropositivity on HCV efficacy and safety. For CHC patients with current HBV infection, the risk of HBV reactivation was present, and monitoring the HBV DNA level during therapy is warranted.